A mathematical model for predicting the pressure drop in a rotating cavity with a tubed vortex reducer. Issue 1 (1st January 2019) - Wei, Song; Yan, Jiaxi; Mao, Junkui; Han, Xingsi; Tu, Zecan
Abstract : The flow characteristics of a tubed vortex reducer, which was used to reduce the pressure drop in an aeroengine air bleed system, were studied in this paper. Accurate prediction of the pressure drop in a rotating cavity with tubed vortex reducer installed is important, but the complex flow structure results in complicated local loss characteristic at the tube entrance, which is difficult to estimate. In this paper, a mathematical model for predicting the pressure drop in a rotating cavity with a tubed vortex reducer was established. For the first time, the effect of the local loss at the tube entrance under rotating conditions was considered, and a method of introducing the local loss factor was established based on a research method applied in traditional rotating orifices. Furthermore, the flow characteristics and the distribution of the static pressure in the tubed vortex reducer cavity were studied by the CFD method and experimental tests, and the pressure information inside the tubed vortex reducer was obtained by detailed experimental testing. This study reveals that the local loss characteristics at the tube entrance are mainly influenced by the incident angle; the closer the incident angle is to 0, the greater the speed coefficient is. The pressure drop at the tube entrance is important and represents approximately 10% of the total pressure drop. The mathematical model shows good accuracy for calculating the pressure drop, with an average error of approximately 2% compared to the experimental data.